The environmental performance of vernacular skywell dwellings in south-eastern China - Duan, Zhongcheng (2012)
Chinese vernacular dwellings are low-energy buildings constructed before the advent of modern external services. No work has been published that incorporates an exacting assessment of the environmental performance of these buildings. The principal aim of this research was to investigate the environmental performance of Chinese vernacular skywell dwellings quantitatively and to establish a model of rigorous and comprehensive qualitative and quantitative research in this area. This was done by analysis of on-site measurements and computer simulation of the environmental performance of eight vernacular skywell dwellings in three villages in south-eastern China - Xidi, Zhifeng and Yuyuan. Environmental performance and building form are examined in relation to current knowledge of the social and economic life of the villages in the past centuries, and to the environmental comfort and the activities of present-day residents of the eight dwellings and other vernacular houses in the villages. It has previously been noted that, in general, the courtyard/skywell of vernacular dwellings decreases in size with progression from northern China to southern China as the climate becomes warmer. However, the mean size of the skywells was found to differ considerably between the three climatically similar villages - large skywells were found in Yuyuan village, medium sized skywells in Xidi village and very small skywells in Zhifeng village. While physical factors were found to be important in determining house form; socioeconomic, cultural and security considerations were found to be strong influences as well. The investigation of the natural illumination of Chinese vernacular dwellings conducted in this study was the first quantitative study of the distribution of natural light in these houses. Houses in the three villages were found to differ in their distribution of illumination according to local skywell form. In all three villages residents were found to take various actions to pursue satisfactory daylighting. Two patterns of daylighting isolux contour in skywell dwellings were identified and analysed. The first comprehensive quantitative study of the thermal performance of Chinese vernacular skywell dwellings was conducted by on-site measurement and administration of questionnaires to residents. Residents of Xidi and Zhifeng were found to appreciate the coolness of their houses in summer, but residents of all three villages found their houses unacceptably cold in winter. The efforts made by residents to mitigate extremes of heat and cold appear to be important in ensuring their thermal comfort. Evidence was obtained that evaporative cooling had a substantial influence on the temperature in the skywells of dwellings in Xidi and Zhifeng villages. In addition to the buffering of temperature by thermal mass, evaporative cooling was found to further reduce the fluctuation in temperature inside the skywell and is likely to have been the main reason that the mean dry bulb temperatures inside the skywells in these villages were lower than the mean external dry bulb temperatures. It is proposed that evaporative cooling in skywells can be exploited even in humid conditions, because natural ventilation can ensure exchange of air between the exterior and the interior of the skywell. Summer temperature/humidity data obtained in the most used spaces of skywell dwellings in the three villages were plotted on psychrometric charts and were examined in relation to the boundaries of predicted thermal comfort zones. The acceptability of thermal conditions in the dwellings that was predicted using this approach was very much lower than that reported by residents. Residents appear to be more tolerant of high humidity with the presence of natural ventilation. Such air movement is desirable to improve the thermal comfort for house occupants in hot and humid conditions.